Experimental Study on Recovery of Copper from Tailings by CCF Flotation Column - Ji Li; Yingchun Huang; Guoyin Ma; Hao Huang (Kuangchan zonghe liyong, 2022)
In this paper, the comprehensive recovery of copper from a magnetic separation tailings in Hubei Province is studied. The process mineralogical study shows that the composition of the tailings is relatively complex, with low copper content of 0.38% and fine disseminated particle size. Copper mainly occurs in primary copper sulfide, with a distribution rate of 74.08%. The copper ore is mainly chalcopyrite, a small amount of copper blue, chalcocite, etc., and the gangue mineral is mainly quartz, the second is calcite, dolomite, sericite, a small amount of feldspar, kaolinite and so on. According to the characteristics of "poor, fine and miscellaneous" copper minerals in tailings, the CCF flotation column was used to carry out the beneficiation test of recovering copper. The results show that after one roughing, one scavenging and two cleaning operations, the copper concentrate with copper grade of more than 16% and copper recovery of more than 76% can be obtained from the tailings containing 0.38% copper. The test index is good, and the comprehensive recovery and utilization of mineral resources can be realized.